Analisa Faktor Pembatas Pertumbuhan Tebu (Saccharum officinarum L.) di Cangkringan, Yogyakarta - Anna Kusumawati; Muhammad Rengga Ibnu Ismail (AGROISTA : Jurnal Agroteknologi, 2022)
This study aims to determine the plant growth parameters that most influence sugarcane productivity. The research was carried out from April 2021 to September 2021 in Argomulyo Village, Cangkringan District, Sleman Regency, Yogyakarta. This research was conducted using a survey method by taking samples of sugarcane stalks at each sampling point. The land area is 3 ha which is divided into 3 blocks, then from each block 10 sugarcane samples are taken so that there are 30 sugarcane samples. Parameters observed in this study were plant height, number of stems, stem diameter, number of leaves, number of internodes, and weight of sugarcane stalks. The results showed that the parameters that had a very high effect on productivity were stem diameter (r=0.986), number of tillers per clump (r=0.908) and sugarcane plant height (r=0.904). Meanwhile, the correlation with sugarcane stalk weight was high (r=0.879), with the number of leaves and cane stem segments very low (r=0.160 and r=0.172). Land productivity in the research location was also much lower than its potential. The addition of organic matter to improve the physical properties of the soil and increase the availability of nutrients was needed so as to increase the growth and productivity of sugarcane.